Kajian Teknis Penentuan Geometri Peledakan Untuk Meningkatkan Nilai Perolehan hasil Peledakan CV. Triaga Nusatama (TNT), Desa Lareh Sago Halaban, Kabupaten Lima Puluh Kota, Sumatra Barat - Gestio Sesar Yulindo; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. Mining activity conducted by CV Triagra Nusatama focused against drilling and blasting. Based on observations and measurements in the field, the geometry of the actual current obtained by blasting fragmentation of rock blasting results size 40-80 cm of 35.41% (calculation of the Split Desktop). Next do the draft geometry blasting to distribution fragmentation optimalisation blasting with a formula of r. l. Ash, ICI-Explosive and the combination of ICI-Explosive formula with adjustments to the conditions of the field. Based on the results of the calculation formula of using fragmentation Kuz-Ram, then the selected geometry proposed blasting II because when viewed from the use of the powder factor and the volume of rock that dismantled proposal II more economical than actual and proposed I, and the results of the fragmentation size 40–80 cm larger generated or the result is desired by the target company. And when compared with geometry proposal III, on geometry III there is a difference of use of explosives fewer, larger volume that is blown, and the resulting fragmentation size 40 – 80 cm larger, but the difference in results the fragmentation size 40–80 cm only 7.07 m3 of proposal IIKeywords:    Blasting, Powder factor, Sliding Rock, Stockpile, Zig-zag Pattern